(untitled) (Research, Society and Development, 2023)
Medicinal plants have played an essential role in the development of human culture. Today, the contribution of plants in industries such as fine chemicals, cosmetics, pharmaceuticals, drugs, and industrial raw materials is remarkable. Recent studies have shown that plants have constituents with functional properties that effectively treat and prevent chronic degenerative diseases. Based on the importance of medicinal plants, this study aimed to quantify the total phenolic content and antioxidant activity of 10 medicinal plants. The phenolic content was quantified using the Swain and Hillis method with a Folin-Ciocalteau reagent, while the antioxidant activity was determined using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) reagent. The samples were dried in a circulating air incubator at 60 ºC for 48 h before phenolic extraction. The compounds were extracted with 50% v/v ethanol, 50% v/v acetone, and distilled water. The results of this study showed that 80% of the plants analyzed had similar phenolic contents that were not statistically different, with an average content of 4.864 mg GAE g-1. The antioxidant activity ranged from 30% to 75%. The ability to scavenge free radicals was expressed as the percentage of inhibition of the oxidation of the radical. In addition, no significant differences were observed in the yield obtained from the extraction solvents, 50% v/v ethanol and 50% v/v acetone, used in this study.